A Novel, Highly Sensitive Quantitative Polymerase Chain Reaction Assay for the Diagnosis of Subarachnoid and Ventricular Neurocysticercosis and for Assessing Responses to Treatment. (21st June 2019) - O'Connell, Elise M; Harrison, Sarah; Dahlstrom, Eric; Nash, Theodore; Nutman, Thomas B
Abstract: Background: Treatment of subarachnoid neurocysticercosis (NCC) is complicated, and assays that can guide treatment are not widely available. The reproducibility and scalability of molecular-based biomarkers would be of great use. Methods: The Taenia solium genome was mined and primers and probes were designed to target repeats with the highest coverage; the most sensitive, specific, and efficient repeat (TsolR13) was selected for clinical testing. We tested 46 plasma samples and 36 cerebral spinal fluid (CSF) samples taken from patients with subarachnoid or ventricular disease using quantitative polymerase chain reaction (qPCR). Results: The analytic sensitivity of TsolR13 was 97.3% at 240 attograms (ag) of T. solium genomic DNA and 100% analytic specificity. The clinical sensitivity in detecting active subarachnoid or ventricular disease in symptomatic patients was 100% in CSF and 81.3% in plasma. The predictive ability to distinguish active from cured disease was better for CSF (94.4% of those cured had negative qPCR results) than for plasma (86.7% of those cured tested negative). Some subjects also had plasma DNA detectable intermittently for years after being cured. Overall, the test performance was equivalent to T. solium antigen detection. Conclusions: A qPCR test for the detection of the highly repetitive Tsol13 sequence has been developed and shown to be highly sensitive and specific for NCC, but also useful as a test of cure in CSF and for the definitive diagnosis of NCC in plasma. Abstract : A new quantitative polymerase chain reaction target, TsolR13, which is highly specific in diagnosing neurocysticercosis when testing plasma and when assessing cerebral spinal fluid, is also a useful biomarker for diagnosing and monitoring patients with subarachnoid neurocysticercosis.